Mandatory CSR expenditure and stock return. Issue 6 (20th April 2020) - Bhattacharyya, Asit; Rahman, Md Lutfur
Abstract : Purpose: India has mandated corporate social responsibility (CSR) expenditure under Section 135 of the Indian Companies Act, 2013 – the first national jurisdiction to do so. The purpose of this paper is to examine the impact of mandated CSR expenditure on firms' stock returns by using actual CSR spending data, whereas the previous studies mostly focus on voluntary CSR proxied by CSR scores. Design/methodology/approach: The authors estimate their baseline regression by using ordinary least squares(OLS) method. Although the baseline regression involving CSR expenditure and stock returns using ordinary least squares method are estimated, endogeneity and reverse causality biases are addressed by using two-stage least squares and generalized method of moments approaches. These approaches contribute mitigating endogeneity bias and biases associated with unobserved heterogeneity and simultaneity. Findings: The findings document that mandatory CSR expenditure has a negative impact on firms' stock returns which supports the "shareholders" expense' view. This result remain robust after controlling for endogeneity bias and the use of both standard and robust test statistics. The authors however observe that this result holds for the firms with actual CSR expenditure equal to the mandated amount but does not hold for the firms with actual CSR expenditure greater than the mandated amount. Therefore, the authors provide evidence that CSR expenditure's impact on stock returns depends on whether firms simply comply the regulation or voluntarily chose an amount of CSR expenditure above the mandated amount. Originality/value: The primary contribution is to present a valid and robust evidence of negative effect of mandated CSR spending on firms' stock returns when the mandatory CSR spending rule is already in place. This study contributes by examining the impact of mandated CSR spending on stock during post-implementation period (2015-2017), whereas other studies by Dharampala and Khanna (2018); Kapoor and Dhamija (2017); and Mukherjee et al. (2018) mainly examined the impact of legislation on Indian CSR. The authors use mandated actual CSR expenditure, whereas previous studies mostly focus on voluntary CSR proxied by CSR scores.